Implementation of K-Means clustering algorithm in mapping the groups of graduated or dropped-out students in the Management Department of the National University - Darwis, Muhammad; Hasibuan, Liyando Hermawan; Firmansyah, Mochammad; Ahady, Nur; Tiaharyadini, Rizka (Universitas Trilogi, 2021)
This study aims to determine the characteristics of students who are likely to graduate or drop out (DO) in the management department of the National University, Jakarta. The study was conducted by implementing the K-Means algorithm, where each data is grouped according to the closest distance to the centroid. Determination of Cluster C1 graduate or C2 drop out is based on the attributes of status of students (active, leave, out and non-active), educational status (graduated or DO), GPA, total credits taken and length of study. To facilitate the clustering process, Orange tools are used that provide K-Means algorithm features. The total data input in this study were 1988 students from various classes. As a result, a pattern or mapping of graduated or DO students was found based on the attributes mentioned earlier. Testing the results of this cluster with the silhouette method, by measuring the distance between cluster members, both C1 and C2, showed good Silhouetter value, reaching 85%. The management department, National University can use the results of this study to predict the graduation of their students.